Evaluating the Contribution of Gastronomy to Regional Tourism in France: A case study of Normandy - Lemercier, Louise (2011)
Destinations have a wide portfolio of tangible and intangibles goods and services; food and drinks are fundamental elements of these assets (Okumus, Okumus and McKercher, 2007). Either as the main determinant or as a secondary importance factor, food plays a considerable role in the motivation and satisfaction of tourist visiting a destination. In this context, food is a fundamental attribute of a destination, and local cuisine can even be part of the uniqueness of a destination (Cohen, 1988, Timothy and Boyd, 2003). Gastronomy can be a viable alternative for destinations which do not benefit from traditional sea, sun and sand, but also a positive asset to complete the existing offer (Quan and Wang, 2004). Nonetheless, the gastronomic market is fierce and many new destinations tend to develop their offers. Thus, some studies have analysed the contribution of gastronomy as part of the tourism offer but very few studies have been led on the real impact of food tourism on a destination. A quantitative approach has been set up in order to determine the contribution of food to regional tourism, the impact of food on the tourist’s satisfaction and motivation in his decision for a destination (Quan and Wang, 2004). Its purpose is also to identify an eventual gastronomic profile, the importance of food in the promotion of the destination and its economic impact. It relies on a case study of Normandy in France, where 240 people have been interviewed, both online and face-to-face. This study tries to bring something new compared to other articles as its focus on a little-explored destination (Normandy) and adapt the methodology developed in Young et al. (2010) to measure the contribution of gastronomy in a destination. Normandy has an undeniable appeal with almost 99% of the sample interviewed wishing to come back in the region. Tourists in Normandy have a positive image of the taste of food in the region compared to average prices. Thanks to Young et al. (2010) methodology, we identified that food is a fundamental element for 14.5% of tourists. Nonetheless, nobody considered food the only reason to come in Normandy. This study did not lead to the identification of a particular food tourist’s profile according to socio-demographic categories. But it distinguishes some profiles regarding activities people do on holidays associated with a particular way of food’s consumption. Normandy should recognise the importance and contribution of food and gastronomy for many reasons. Indeed, even if gastronomy is not quoted as the main determinant in the tourist decision, it is part of every tourist’s experience and contributes to their overall satisfaction. Food represents an undeniable economic impact on the region. Despite a small proportion of interviewees in contact with the destination’s promotion, people know what they can expect and do. Food and drinks are part of the overall images tourists have of Normandy, alongside with countryside and culture and heritage. Nonetheless, Normandy is not exploiting this asset to its maximum and there are still many things that could be improved to overcome some of the issues (languages’ barrier, promotion’s efficiency, initiation into French tastes, prices, quality and origins, etc.).